Egypt Family Planning Method Mix Indicates Shifting toward Hormonal Contraceptives - Wahby, Ghada; Sabry, Hend; Abdel-Razik, Madiha; Salem, Marwa Rashad; EL Aguizy, Fayrouz (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The study is of practical importance for policy makers and family planning (FP) program managers as the profile of FP method-mix with a shift from a mechanical method as intrauterine devices (IUD) to hormonal methods such as oral contraceptives (OCs) and injectables predicts a critical situation for maternal and child health and reflects shortcomings in FP service delivery program. AIM: The purpose of the current study was to identify reasons for the progressive shift from IUD to OCs in Egypt. METHODS: The study is an-operations research conducted at four levels of the Ministry of Health and Population/FP (MOHP/FP) service delivery: Central (headquarter, HQ), governorate, district, and service delivery points. It included five of MOHP/United Nations Fund for Population Activities-Contraceptive Security Project governorates that represent, urban governorates, Lower Egypt, and Upper Egypt. Both qualitative data in-depth interviews with MOHP/HQ staff, Two Focus Group Discussions with FP Health Directorates staff and nurses in the five governorates, and quantitative data through a self-administered questionnaire for 607 service providers (SP). RESULTS: There was a consensus on the actual shift from IUD to OCs use. Reasons were the absence of incentives for healthcare providers for IUD insertion services (64%) and improper training of physicians (45%), and the availability of OCs all time. CONCLUSION: The three articulating issues that lead to shifting from IUD to OCs are: Unsatisfactory training and incentive systems for SPs and the clients’ choice of OCs for independent use/autonomy, and availability of OCs all the times at a reasonable cost in both the public and private sectors.